Differential Metabolic Rearrangements after Cold Storage Are Correlated with Chilling Injury Resistance of Peach Fruits - Bustamante, Claudia A.; Monti, Laura L.; Gabilondo, Julieta; Scossa, Federico; Valentini, Gabriel; Budde, Claudio O.; Lara, María V.; Fernie, Alisdair R.; Drincovich, María F. (Frontiers in Plant Science, 2016)
Reconfiguration of the metabolome is a key component involved in the acclimation to cold in plants; however, few studies have been devoted to the analysis of the overall metabolite changes after cold storage of fruits prior to consumption. Here, metabolite profiling of six peach varieties with differential susceptibility to develop mealiness, a chilling-injury (CI) symptom, was performed. According to metabolic content at harvest; after cold treatment; and after ripening, either following cold treatment or not; peach fruits clustered in distinct groups, depending on harvest-time, cold treatment, and ripening state. Both common and distinct metabolic responses among the six varieties were found; common changes including dramatic galactinol and raffinose rise; GABA, Asp and Phe increase; and 2-oxo-glutarate and succinate decrease. Raffinose content after long cold treatment quantitatively correlated to the degree of mealiness resistance of the different peach varieties; and thus, raffinose emerges as a candidate biomarker of this CI disorder. Xylose increase after cold treatment was found only in the susceptible genotypes, indicating a particular cell wall reconfiguration of these varieties while being cold-stored. Overall, results indicate that peach fruit differential metabolic rearrangements due to cold treatment, rather than differential metabolic priming before cold, are better related with CI resistance. The plasticity of peach fruit metabolism renders it possible to induce a diverse metabolite array after cold, which is successful, in some genotypes, to avoid CI